8
$\begingroup$

Can anyone help me attain the result for the following series?

$$\sum_{n=2}^{\infty} \frac{(-1)^n \zeta(n)}{n(n+1)}= \frac{1}{2} \left( \log 2 + \log \pi +\gamma -2 \right)$$

I don't know how to start. I am seriously thinking that this can be done using residues or contour integration since with real analysis I cannot see a pattern.

$\endgroup$
  • 3
    $\begingroup$ Can this be of help? Not exactly the same, but it might give you some inspiration. $\endgroup$ – Daniel R Jun 5 '15 at 7:48
  • $\begingroup$ Perhaps, I'll take a look! Thanks! $\endgroup$ – Tolaso Jun 5 '15 at 8:42
  • 1
    $\begingroup$ @DanielR It seems like a good start. $\endgroup$ – Tolaso Jun 5 '15 at 8:46
7
$\begingroup$

Take the logarithm of the Weierstass product form of the Gamma function $$ \frac{1}{\Gamma(x)}=xe^{\gamma x}\prod_{n=1}^\infty \left( 1+\frac{x}{n}\right)e^{-x/n}$$ to obtain $$-\log\Gamma(x)=\log x+\gamma x+\sum_{n=1}^\infty \log\left(1+\frac{x}{n}\right)-\frac{x}{n}$$ Now, $$\sum_{n=1}^\infty \log\left(1+\frac{x}{n}\right)-\frac{x}{n} =-\sum_{n=1}^\infty\sum_{m=2}^\infty\frac{\left(-\frac{x}{n}\right)^m}{m} \\\\=-\sum_{m=2}^\infty\frac{(-1)^m x^m}{m}\sum_{n=1}^\infty\frac{1}{n^m}=-\sum_{m=2}^\infty\frac{(-1)^m x^m \zeta(m)}{m}$$ so that $$\sum_{n=2}^\infty\frac{(-1)^n \zeta(n)}{n}x^n=\gamma x+\log(x)+\log\Gamma(x)$$ and $$\sum_{n=2}^\infty\frac{(-1)^n \zeta(n)}{n(n+1)}=\int_{0}^{1}(\gamma x+\log(x)+\log\Gamma(x))dx=\frac{\gamma}{2}-1+\int_{0}^{1}\log\Gamma(x)dx$$ $\int_{0}^{1}\log\Gamma(x)dx=\log\sqrt{2\pi}$ is quite famous. check here for reduction to evaluating $\int_0^\pi \log\sin(x)dx$ and here for the evaluation

$\endgroup$
  • 1
    $\begingroup$ That is amazing. Thank you. I manages to derive the identity: $$\sum_{n=2}^\infty\frac{(-1)^n \zeta(n)}{n}x^n=\gamma x+\log(x)+\log\Gamma(x)$$ using the link above, but then I was too tired to construct the wanted series. (actuall I did not see that it was related to the integral) $\endgroup$ – Tolaso Jun 5 '15 at 11:54
0
$\begingroup$

it it not difficult to show that $$\sum _{k=2}^{\infty } \frac{\pi (-x)^k \zeta (k)}{k (k+1)}=\int_0^{\infty } -\frac{(t-2 i \pi x) \log \left(1+\frac{i t}{2 \pi x}\right)+(t+2 i \pi x) \log \left(1-\frac{i t}{2 \pi x}\right)-2 t}{\left(e^t-1\right) (4 \pi x)} \, dt+\frac{1}{2} (-\pi \log (x)+\pi -\pi \log (2 \pi ))+\frac{1}{4} (-2 \gamma \pi x+3 \pi x-2 \pi x \log (x))$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.